2022
DOI: 10.3390/dj10070120
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Vitamin D Supplementation as Non-Surgical Treatment for Periodontal Disease with a Focus on Female Patients: Literature Review

Abstract: Periodontal disease is a complex disease that involves an imbalance between the oral microbiota and an individual’s inflammatory response. Moreover, the inflammatory response contributes to further imbalance; if left untreated, periodontal disease may result in tooth loss. Vitamin D is intricately involved in the regulation of calcium–phosphate homeostasis and bone mineral metabolism; considering that periodontal surgery usually includes regenerative therapy, adequate vitamin D and calcium levels are essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…[ 27 ] proposed that the gingivitis score changes in direct proportion to the dosage of vitamin D supplementation. [ 28 ] They observed that gingival score (baseline) every month comparing the baseline gingivitis score with later visits after the patient was given the oral vitamin D supplementation dosages from 500 to 2000 IU with results better with higher dosages ( P < 0.0001). There is no clear evidence that vitamin D can prevent periodontitis or that this association is the cause.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 ] proposed that the gingivitis score changes in direct proportion to the dosage of vitamin D supplementation. [ 28 ] They observed that gingival score (baseline) every month comparing the baseline gingivitis score with later visits after the patient was given the oral vitamin D supplementation dosages from 500 to 2000 IU with results better with higher dosages ( P < 0.0001). There is no clear evidence that vitamin D can prevent periodontitis or that this association is the cause.…”
Section: Discussionmentioning
confidence: 99%
“…They can prevent and enhance the treatment of periodontitis as well [23]. Also, calcium supplementation can positively affect the management of periodontal disease [24]. Moreover, optimal calcium content can decelerate tooth loss and alveolar ridge resorption [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium plays a crucial role in many aspects of human health, including the formation and metabolism of bones, the activation of clotting factors, and the regulation of blood pressure and nerve functions [ 1 , 2 , 3 , 4 , 5 , 6 ]. Dietary calcium deficiency is a worldwide public health concern [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%